2010
DOI: 10.1002/smll.200901067
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of pH‐Switchable Spiral Tubes: Supramolecular Chemical Springs

Abstract: Spiral organic tubes are prepared by self‐assembly of lithocholic acid in aqueous solution at pH 12.0. The tubes can transition into a straight shape as the pH of solution is reduced to 7.4. The shape transition of the tubes is reversible as the pH of solution is adjusted back to 12.0 (see image). The pH‐switchable shape transition suggests that the self‐assembled organic tubes can act as a supramolecular chemical spring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 36 publications
4
65
0
2
Order By: Relevance
“…The latter transition was not observed for other oligomers, reflecting their more stable micellar state in aqueous solutions even when the stabilizing chains are very short. Due to its low solubility, lithocholic acid is the least studied bile acid, but recent reports on its complex self-assembly [28,34,35] have shown that its behavior in aqueous solutions is still far from being well understood. The ''double thermosensitivity'' arising both from the salt-dependent LCST of oligo(ethylene glycol) and the temperature-responsive self-assembly of neutral amphiphilic bile acid derivative provides an interesting concept for bile acid-based smart materials, and thus warrants further studies on the self-assembling characteristics of lithocholate-based oligomer.…”
Section: Resultsmentioning
confidence: 99%
“…The latter transition was not observed for other oligomers, reflecting their more stable micellar state in aqueous solutions even when the stabilizing chains are very short. Due to its low solubility, lithocholic acid is the least studied bile acid, but recent reports on its complex self-assembly [28,34,35] have shown that its behavior in aqueous solutions is still far from being well understood. The ''double thermosensitivity'' arising both from the salt-dependent LCST of oligo(ethylene glycol) and the temperature-responsive self-assembly of neutral amphiphilic bile acid derivative provides an interesting concept for bile acid-based smart materials, and thus warrants further studies on the self-assembling characteristics of lithocholate-based oligomer.…”
Section: Resultsmentioning
confidence: 99%
“…1b) interactions upon addition of NaCl [24]. Some other kind of NaLC tubules with a larger cross section were reported to form by lowering the pH of a basic solution via a reversible peculiar spiral to straight tubule transition [25].…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…Since the β-LTrpC micelles were similar to those formed by HC (the natural precursor) in analogous conditions, in terms of both size and shape [28], an ionization degree α of 0.8 was used in the calculations, according to the α values (0.79-0.85) usually reported for the micelles formed by the precursor [57][58][59]. A n agg value of 6.4 ± 0.1 was estimated, in agreement with the range of n agg values (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) reported in the literature for the HC micelles [57,60]. The N Hyd value of 41±5 was inferred from the n agg value by assuming the prolate ellipsoidal geometry.…”
Section: Self-assembly Of -L-trpc In Alkaline Solutionsmentioning
confidence: 99%
“…Tubules [12,13], fibrils [14] and globular [15][16][17][18] or elongated micelles [19][20][21] were extensively reported in the literature. Moreover, BAs are widely used as starting materials in the preparation of synthetic derivatives.…”
Section: Introductionmentioning
confidence: 98%